Wan-Nian-Qing, a Herbal Composite Prescription, Suppresses the Progression of Liver Cancer in Mice by Regulating Immune Response - Zhang, Xinrui; Liu, Xin; Zhang, Yue; Yang, Anhui; Zhang, Yongfeng; Tong, Zhijun; Wang, Yingwu; Qiu, Ye (Frontiers in Oncology, 2021)
The Wan-Nian-Qing prescription (WNQP), an herbal composite containing Ornithogalum caudatum, has been used in China for several years for cancer treatment. However, the mechanism of its pharmacological action against liver cancer is not clear. This study aimed to investigate the role of WNQP in inhibiting tumor growth in hepatocellular carcinoma model mice and determine its mechanism of action. We established HepG2- and SMMC-7721-xenografted tumor models in nude mice and BALB/c mice. The mice were administered WNQP for 2 weeks. The bodyweight of each mouse was monitored every day, and the tumor size was measured using vernier caliper before each round of WNQP administration. After the last dose, mice were sacrificed. The tumors were removed, lysed, and subjected to proteome profiling, enzyme-linked immunosorbent assay, and western blotting. The liver, spleen, and kidney were collected for histopathological examination. The effects of WNQP against liver cancer were first systematically confirmed in HepG2- and SMMC-7721-xenografted nude mice and BALB/c mice models. WNQP inhibited tumor growth, but failed to affect bodyweight and organ structures (liver and spleen), confirming that it was safe to use in mice. In BALB/c mice, WNQP regulated immune function, inferred from the modulation of immune-related cytokines such as interleukins, interferon, tumor necrosis factors, and chemokines. Further results confirmed that this regulation occurred via the regulatory effects of WNQP on Nrf2 signaling. WNQP can inhibit the growth of HepG2- and SMMC-7721-xenografted tumors in nude mice and BALB/c mice. This effect manifests at least partially through immunomodulation mediated apoptosis.